Massive gingival enlargement in a nine-year-old paediatric patient: A rare case report - Pallavi Chaubey; Saurav Chandra; Mohammed Ahsan Razi; Seema Qamar (Wolters Kluwer Medknow Publications, 2021)
Gingival enlargement (GE) is a well-known clinical phenomena with the primary aetiology being plaque and poor oral hygiene. Many reasons for GE have been known. Most of the time good oral hygiene is sufficient to achieve normal healthy gingiva. GE is a heterogeneous group of disorder characterized by progressive enlargement of the gingiva with an increase in submucosal connective tissue elements. Some of them are inherited and iatrogenic while others are idiopathic. In this case, we report a case with massive idiopathic GE in a 9-year-old female child; treatment received, histopathological description and follow-up are discussed.